Creation of miRNA-loaded, mesenchymal stem cell derived microparticles as targeted cancer therapy - Prokopi, Marianna; Pitsillides, Costas; Kapnisis, Konstantinos; Anayiotos, Andreas; Kousparou, Christina; Epenetos, Agamemnon (My University, 2015)
The project describes a new class of therapeutic agents, based on microparticles (MPs) derived from mesenchymal stem cells (MSCs) that can selectively target tumours in vivo.containing and delivering miRNAs that affect the action of genes associated with cancer growth, neovascularisation and metastasis applicable for both local and systemic administration. MSCs isolated from the Wharton’s jelly of human umbilical cords were used to generate MPs from the membrane of MSCs as intact vesicles. The MSC-derived MPs were harvested and characterized by SEM, PCR, FACS and Fluorescence Microscopy. Different cancer cell lines (breast, colon, ovarian adenocarcinoma) were exposed to MPs and the response to treatment was evaluated by cell morphology, proliferation, migration, gene expression and apoptosis. The therapeutic potential of MPs was tested in vivo in orthotopic tumor mouse models using in vivo flow cytometry and whole body fluorescence-bioluminescence to dynamically investigate the biodistribution and homing kinetics of MPs in mice. In vitro experiments confirmed that MSC-derived MPs can be internalised by cancer cells and induce a biological effect as evidenced by damage/shrinkage of the recipient cell, induction of apoptosis, inhibition of cell proliferation and tumor growth attenuation in a dose-dependent manner. In vivo studies monitored and quantified fluorescently labelled MPs in circulation and detected the biodistribution and incorporation in cells and organs in healthy and tumor-bearing mice. MSC-MPs containing miRNAs possess tumor inhibitory properties, transfer miRNAs and affect the action of cancer genes.
Keywords: Therapeutic agents; Microparticles; Mesenchymal stem cells